Dual Roles of OsGH3.2 in Modulating Rice Root Morphology and Affecting Arbuscular Mycorrhizal Symbiosis - Liu, Cheng-Chen; Liu, Ying-Na; Cheng, Jian-Fei; Guo, Rui; Tian, Li; Wang, Bin (Frontiers in Plant Science, 2022)
Several angiosperm GRETCHEN HAGEN 3 (GH3) genes, including tomato SlGH3.4 and rice OsGH3.2 are induced during arbuscular mycorrhizal (AM) symbiosis, but their functions remain largely unclear. Recently, tomato SlGH3.4 was suggested to negatively regulate arbuscule incidence via decreasing auxin levels in colonized cells. In this study, by acquiring rice OsGH3.2pro::GUS transgenic plants and generating Osgh3.2 mutants via CRISPR/Cas9 technique, the roles of OsGH3.2 in modulating rice root morphology and affecting AM symbiosis were investigated through time course experiments. Unlike SlGH3.4, OsGH3.2 showed asymbiotic expression in rice young lateral roots, and its mutation resulted in a ‘shallow’ root architecture. Such root morphological change was also observed under symbiotic condition and it likely promoted AM fungal colonization, as the mutants exhibited higher colonization levels and arbuscule incidence than wild-type at early stages. Similar to SlGH3.4, OsGH3.2 showed symbiotic expression in cortical cells that have formed mature arbuscules. At late stages of symbiosis, Osgh3.2 mutants showed elongated cortical cells and larger arbuscules than wild-type, indicating elevated auxin level in the colonized cells. Together, these results revealed both asymbiotic and symbiotic roles of OsGH3.2 in modulating rice root architecture and controlling auxin levels in arbusculated cells, which further affected colonization rate and arbuscule phenotype.